TAUBAT DALAM PERSPEKTIF HADITS - Sam’ani Sya’roni (UIN K.H. Abdurrahman Wahid Pekalongan, 2009)
As the perfect creature, human beings have naturally good nearness and harmony either with their God or among them. This natural tendency, however, is often depraved by themselves by committing a sin or break norm. The fadedness of this natural tendency makes them suffering in their whole life. Therefore, there is no other way unless seeking medicine and solution, i.e. repenting or al-taubah al-shâdiqah or taubatan nasûha.